2023
DOI: 10.3389/fpsyg.2023.1090775
|View full text |Cite
|
Sign up to set email alerts
|

On the intercultural sensitivity of university students in multicultural regions: A case study in Macao

Abstract: Intercultural sensitivity has been regarded as a very important ability necessary for living in multicultural countries and regions. In this research, the quantitative method was used to explore the intercultural sensitivity of university students in Macao, a typical multicultural region in China. By adopting the Intercultural Sensitivity Scale developed by Chen and Starosta and a sociodemographic questionnaire designed by the authors, this study investigated the intercultural sensitivity level of university s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Furthermore, the results of Penbek et al's study do not align with the results of the current study in terms of the international experience since no significant difference was found regarding being abroad within the body of this study. Chen and Hu (2023) also sought to investigate the level of intercultural sensitivity exhibited by university students in Macao, a region in China that is known for its multiculturalism. The findings indicated that university students in Macao exhibited a relatively high level of intercultural sensitivity, which is consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the results of Penbek et al's study do not align with the results of the current study in terms of the international experience since no significant difference was found regarding being abroad within the body of this study. Chen and Hu (2023) also sought to investigate the level of intercultural sensitivity exhibited by university students in Macao, a region in China that is known for its multiculturalism. The findings indicated that university students in Macao exhibited a relatively high level of intercultural sensitivity, which is consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Individual variables such as English proficiency and intercultural experiences have been studied in relation to the development of IC in Chinese settings. Chen and Hu (2023) discovered a significant correlation between Chinese undergraduates' intercultural sensitivity and language proficiency. Unlike the study by Wu (2016), Weng (2018), and Huang (2021) found no significant relationship between IC development and English proficiency.…”
Section: Affective Dimensionmentioning
confidence: 99%
“…Chen and Starosta's ISS (2000) have been widely utilised in various professional and cultural contexts to measure intercultural sensitivity. Previous research has employed the ISS to measure intercultural sensitivity among individuals in fields such as education (Demir & Kiran, 2016) and hospitality (Yurur et al, 2018), as well as in different cultural contexts like Taiwan (Wu, 2015), Macao (Chen & Hu, 2023), and Algeria (Boudouaia et al, 2022).…”
Section: Chen and Starosta's (2000) Intercultural Sensitivity Scalementioning
confidence: 99%
“…In an increasingly interconnected and globalised world, navigating interactions with individuals from diverse cultures is essential (Hur et al, 2020;Ozer et al, 2021). Travelling abroad provides a unique opportunity to engage with different societies and foster intercultural sensitivity (Chen & Hu, 2023). In the context of higher education, academic institutions have recognised the significance of equipping students with the necessary skills to navigate intercultural encounters, a crucial aspect of their forthcoming entry into the job market (Sonnenschein & Ferguson, 2020).…”
Section: Introductionmentioning
confidence: 99%